Understanding technological, cultural, and environmental motivators explaining the adoption of citizen science apps for coastal environment monitoring - Cardoso-Andrade, Mariana (2022)
Cardoso-Andrade, M., Cruz-jesus, F., Souza Troncoso, J., Queiroga, H., & Gonçalves, J. M. S. (2022). Understanding technological, cultural, and environmental motivators explaining the adoption of citizen science apps for coastal environment monitoring. Global Environmental Change, 77, 1-17. [102606]. https://doi.org/10.1016/j.gloenvcha.2022.102606--- Funding: This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia): CESAM through projects UIDP/50017/2020, UIDB/50017/2020, and LA/P/0094/2020; CCMAR through projects UIDP/04326/2020, UIDB/04326/2020, and LA/P/0101/2020; and Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS through project UIDB/04152/2020. Mariana Cardoso-Andrade also wishes to acknowledge the financial support of FCT through the doctoral grant PD/BD/143087/2018.